1642 Va. Acts 255, Act 23 - (:unkn) unknown (General Publisher, 1642)
Be it also enacted and confirmed, that what person or persons soever shall sell or barter with any Indian or Indians for piece, powder and shot and being thereof lawfully convicted, shall forfeit his whole estate
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES